Integrating data from spontaneous and induced trans-10 shift of ruminal biohydrogenation reveals discriminant bacterial community changes at the OTU level - Enjalbert, Francis; Zened, Asma; Cauquil, Laurent; Meynadier, Annabelle (Frontiers in Microbiology, 2023)
Microbial digestion is of key importance for ruminants, and disturbances can affect efficiency and quality of products for human consumers. Ruminal biohydrogenation of dietary unsaturated fatty acids leads to a wide variety of specific fatty acids. Some dietary conditions can affect the pathways of this transformation, leading to trans-10 fatty acids rather than the more usual trans-11 fatty acids, this dysfunction resulting in milk fat depression in dairy cows. Here, we combined data from induced and spontaneous trans-10 shift of ruminal biohydrogenation, providing new insight on bacterial changes at different taxonomic levels. Most changes related to bacterial genera that are not known to be involved in the biohydrogenation process, showing that the trans-10 shift is only the biochemical marker of a wide change of bacterial community. At OTU level, sparse discriminant analysis revealed strong associations between this change of biohydrogenation pathway and some taxa, that could both be microbial markers of this disturbance and candidates for studies relative to their ability to produce trans-10 fatty acids.